The Power of Global Economic Forces on Islamic Stock Returns in Indonesia: Storm or Opportunity? - Nurmasari, Nuraini Desty; Ansari, Rizal (Journal of Islamic Economic and Business Research, 2025)
This study examines the effect of U.S. monetary policy, risk aversion, and foreign capital flows on stock returns in the Indonesian Islamic Stock Market for the period 2017-2021using the Autoregressive Distributed Lags (ARDL) approach. The results of this study indicate that the U.S. monetary variable is positive in the short term and negative in the long term. Expansionary U.S. monetary policy positively affects the increase in stock returns, but in the extended run, stock returns fall along with contractionary U.S. monetary policy shocks. Risk aversion in the short term is insignificant but positively significant in the long term. Meanwhile, short- and long-term foreign capital flows positively affect stock returns. Foreign investors will first analyze the risk before investing in the ISSI index. Global risk aversion is the main factor driving the increase in foreign capital inflows into the ISSI index. This research is expected to provide recommendations for investors and policymakers. Investors must closely observe essential macroeconomic indicators since these exert substantial long-term influence on ISSI performance, whereas short-term implications may be less relevant. For policymakers, ensuring macroeconomic stability primarily through regulating currency rates and money supply is crucial for cultivating a stable investment climate and promoting the expansion of the Islamic financial industry.